2018
DOI: 10.1002/cpt.1267
|View full text |Cite
|
Sign up to set email alerts
|

A Model‐Based Approach to Quantify the Time‐Course of Anti‐Drug Antibodies for Therapeutic Proteins

Abstract:  The use of therapeutic proteins has increased dramatically for a wide range of diseases. The immunogenicity is an important factor because the formation of ADAs can cause adverse events and/or diminished efficacy. However, few studies directly quantified the time profiles of ADA levels. WHAT QUESTION DID THIS STUDY ADDRESS? The study was aimed to quantitatively describe the time course of ADA titers in response to the treatment of therapeutic proteins and to explore the relationship between titers and incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The immunogenic response is a modeling challenge because ADA assays often do not quantify concentrations, only titers of ADA molecules. 42 As a first step toward quantifying the response, the ADA-negative PK data for infliximab available in literature combined with the parameterization of the time course of ADA formation in humans by Ren et al 36 have enabled the first mechanistic representation of the immunogenic response to a therapeutic drug product. Figure S2 displays the simulated profile of mean ADA formation following first dose administration in a typical population of adults with inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The immunogenic response is a modeling challenge because ADA assays often do not quantify concentrations, only titers of ADA molecules. 42 As a first step toward quantifying the response, the ADA-negative PK data for infliximab available in literature combined with the parameterization of the time course of ADA formation in humans by Ren et al 36 have enabled the first mechanistic representation of the immunogenic response to a therapeutic drug product. Figure S2 displays the simulated profile of mean ADA formation following first dose administration in a typical population of adults with inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of additional data, the zero order molar synthesis rates of IgM and IgG were assumed equal (knormalsynnormalIgM=knormalsynnormalIgG). The typical ADA profile featured an initial period of IgM synthesis, a lag phase, and finally a sustained IgG response . The group noted differences in IgG degradation rates between healthy and autoimmune individuals, which were implemented in the model .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the simulations, the lag time (t lag ) to ADA production was set to a literature value of 4 weeks. [4][5][6] The production rate of ADA (P ADA ) was assumed to be a saturable function of the time (Equation 5) rather than the accumulated biologic dose, as the literature reported that the amount of ADA was relatively independent on the accumulated drug exposure. 2 ADA subsequently enters the central compartment (ADA C ) after going through 5 transit compartments (ADA T1 to ADA T5 ) with a same transit rate constant of K T (Equations 6-10).…”
Section: Pk Models For Simulationmentioning
confidence: 99%